End-to-side neurorrhaphy with and without perineurium - Fausto Viterbo; Teixeira, Evandro; Hoshino, Katsumae; Padovani, Carlos Roberto (São Paulo Medical Journal, 1998)
OBJECTIVE: We compared end-to-side neurorraphy with and without the perineural sheath. METHOD: Twenty rats were used. The peroneal nerve was sectioned and the distal end was sutured to the lateral face of the tibial nerve. We removed the perineural sheath only on the right side, but not on the left side. The proximal end of the peroneal nerve was curved back approximately at a 100° angle and implanted into the adductor muscle. Six months later, the 14 surviving animals were submitted to electrophysiological tests, sacrificed, and the nerves and muscles were taken for histological exams. RESULTS: On the right side, the muscles that had positive response needed an average of 258.89 mV (±92.31) of electric stimulus and on the left side 298.34 mV (±139.32). The average weight of the tibial cranial muscles of the right side was 0.47 g (0.18) and for the left side 0.45 g (0.15). The distal end of the peroneal nerve showed averages of 310.29 (±191.34) nerve fibers on the right side and 287.71 (±183.60) on the left side. The tibial nerve above the neurorraphy showed averages of 939.46 (±223.51) nerve fibers on the right side and 959.46 (±327.48) on the left side. The tibial nerve below the neurorraphy showed averages of 935.17 (±298.65) nerve fibers on the right side and 755.31 (±323.26) on the left side. The average areas of the right tibial cranial muscles were 0.0162 m2 (±0.008), after 230 magnification, and 0.0152 m2 (0.0064) for the left tibial cranial muscles. The histological features of the tibial cranial muscles, taking normal as 100%, were 78.21 (±20.75) on the right side and 82.14 (±15.89) on the left side. The statistical analysis (Student’s t test) did not reveal any difference (p>0.05) among right and left sides for all variables. CONCLUSION: The authors concluded that the two neurorraphies (with and without perineurium) did not show any difference regarding morphological and electrophysiological features studied.